Change management in International Islamic University Malaysia (IIUM) - Shaharudin, Mir Azrul (Invention Journals, 2019)
Change is vital to any institution in order to compete in the challenging world. International Islamic University Malaysia (IIUM) was establish more than 35 years ago with a clear vision to become a leading international centre of education excellence for Muslims around the world in all branches of knowledge. In its early years, the university manage to lift up its vision and mission as the beacon for Islamic knowledge. However, after a quarter of a century, their existence began to fade. Competition from other universities, ranking system and political influences had shifted the focus of IIUM. Nonetheless, the new Malaysia after its 14th General Election had resulted changes in the country’s education system and affected IIUM directly. New management team was brought in and changes becoming to take place in the university. IIUM is set to return as the leading international centre of education excellence for Muslim with vigorous change management processes.